Peran Kepuasan Pelanggan Dalam Memediasi Pengaruh Perceived Value Terhadap Loyalitas Pelanggan Di Toko R-Style Kota Metro - Arkham, Amirul Alfi; Fuadi, Selamet (Jurnal Manajemen DIVERSIFIKASI, 2023)
The purpose of this study was to determine the mediating role of customer satisfaction in mediating perceived value on customer loyalty. While the research design uses quantitative mediation methods from path analysis, the respondents used from the calculation sample are 84 respondents during the 7-day study. The sampling technique used purposive sampling and data collection using a questionnaire questionnaire given to consumers who frequently made purchase transactions during the 7 days of the study. The analytical tools used are simple regression analysis and multiple multiple regression with the path analysis coefficient decision and partial t and the coefficient of determination. The results of the research prove that the perceived value of customer satisfaction which is a series of values ​​felt by customers from a model or product which is then used as an evaluation material so that customers have a certain commitment in their buying behavior, then the emotional response in the form of feelings of pleasure and relief because it has been fulfilled or fulfilled. desire after making a purchase of a product/service. Keywords: customer satisfaction, perceived value, customer loyalty.